(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Intestinal perforation, defined as a loss of continuity of the bowel wall, is a potentially devastating complication that may result from a variety of disease processes. Abdominal trauma, instrumentation, inflammation, infection, cancer, ischemia, and blockage are among the common causes of perforation. The morbidity and possible death of peritonitis, as well as its systemic after effects due to the leakage of intestinal contents, must be avoided by early detection and swift treatment1.